INTEGRASI SERVQUAL DAN QUALITY FUNCTION DEPLOYMENT UNTUK PENGUKURAN KUALITAS LAYANAN (STUDI KASUS: PROGRAM STUDI PENDIDIKAN TEKNIK MESIN, UNIVERSITAS PALANGKA RAYA) - Wiyogo, Wiyogo; Surachman, Surachman; Soenoko, Rudy; Setyanto, Nasir Widha (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2013)
Services in Program Studi Pendidikan Teknik Mesin (PSPTM) still has drawbacks, among other complaints for cleanliness wc, and class. This indicates or identifies a student dissatisfaction against poor service. Service has 5 dimensions, namely tangible dimension, responsiveness, reliability, assurance, empathy is to be seen to solve the existing problems. Analytical techniques is used SERVQUAL approach and Quality Function Deployment (QFD). Calculation results gap between perception and expectation would then be prioritized using the Pareto principle to acquire the attributes which are important for repair. In the academic service attributes availability of toilets has the highest gap value at -2,70 , while at the administrative service, on-time attendance officer has a gap value of -1,74. From the House of Quality on academic services obtained 33 attributes as recommendations for improvements such as fixing a broken toilet, maximize existing bandwidth. Meanwhile, in the administrative services generated 21 attributes priority, such as scheduling workers, implementing SOP service, encourage officers to be more proactive in serving students.Â